Pengembangan E-book Berbasis Android Menggunakan Sigil 0.9.13 Pada Mata Kuliah Ekologi Hewan Untuk Mahasiswa Biologi Universitas Negeri Padang - Zalik Muhammad Latif; Abdul Razak; Lufri; Moralita Chatri (Postgraduate, University of Mataram, 2024)
The purpose of this research is to produce an android based ebook in Animal Ecology courses that is valid, practical and effective. This research is research and development using the Plomp model. The results of the validation assessment by the validator of the android-based e-book in the Animal Ecology course showed an average value of 82.33% (very valid). The results of the practicality assessment by lecturers of the Animal Ecology course showed an average value of 81.5% (very practical) and student assessment results obtained an average value of 91.64% (very practical). The results of the effectiveness test of Android-based e-books show that Android-based e-books are very effective. Thus, it can be concluded that the developed Android-based e-book is very valid, very practical, and very effective.